Contribution to the Taxonomy and Host-Relations of the Genus Serratacarus (Trombidiformes: Trombiculidae) - De Castro Jacinavicius, Fernando (2021)
The genus SerratacarusGoff and Whitaker 1984, currently includes only two species, Serratacarus dietzi Goff and Whitaker, 1994 and Serratacarus lasiurus Goff and Whitaker, 1994, which were recorded on cricetid rodents from natural reserve areas of Brazil. Here, we provide a review of the morphological characters for both species and synonymize of the species Trombewingia brasiliensisGoff and Gettinger, 1991 with S. lasiurus. Additionally, we provide new locality records for both species and the first record for S. dietzi on southeastern four-eyed opossum, Philander frenatus Olfers, 1818 (Didelphimorphia, Didelphidae).